Information, evolution and utility - Jeroen M. Swinkels; Larry Samuelson (Theoretical Economics, 2006)
Human utility embodies a number of seemingly irrational aspects. The leading example in this paper is that utilities often depend on the presence of salient unchosen alternatives. Our focus is to understand why an evolutionary process might optimally lead to such seemingly dysfunctional features in our motivations and to derive implications for the nature of our utility functions.
Keywords: C70; C72; D80; D82; 330; Evolution; information; internal conflict; self control; temptation; time consistency; utility